Ten years and counting: preserving and sharing Colorado's agricultural history online - Watson, Renae, J., author; Level, Allison V., author; Oehlerts, Beth, author (Colorado State University. Libraries, 2018)
Colorado State University Libraries (CSUL) supports the preservation of agricultural history, as evidenced by their participation in the Preserving the History of United States Agriculture and Rural Life: State and Local Literature, 1820-1945 project, administered by Cornell University. This article reviews CSUL's work on this preservation project, including digitization of historical agriculture-related documents. CSUL's latest effort to keep agricultural literature relevant and accessible includes moving the Colorado Agriculture Bibliography website to Springshare's LibGuides platform (https://libguides.colostate.edu/agbib). Advantages and challenges of using the LibGuides platform for the promotion and sharing of such collections are discussed.
Preserving and sharing Colorado's agricultural history online
Preprint manuscript.
Publisher version: https://doi.org/10.1080/10496505.2019.1576529
Keywords: agricultural documents; LibGuides; USAIN; NEH grant; digitization